2016
DOI: 10.1073/pnas.1606610113
|View full text |Cite
|
Sign up to set email alerts
|

Changes in active site histidine hydrogen bonding trigger cryptochrome activation

Abstract: Cryptochrome (CRY) is the principal light sensor of the insect circadian clock. Photoreduction of the Drosophila CRY (dCRY) flavin cofactor to the anionic semiquinone (ASQ) restructures a C-terminal tail helix (CTT) that otherwise inhibits interactions with targets that include the clock protein Timeless (TIM). All-atom molecular dynamics (MD) simulations indicate that flavin reduction destabilizes the CTT, which undergoes large-scale conformational changes (the CTT release) on short (25 ns) timescales. The CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
87
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 40 publications
14
87
1
1
Order By: Relevance
“…the first, structure from the ensemble was used to initiate the method. Following [45], in the molecular alignment step only residues with a root mean square fluctuation of less than 1.3 Å were considered. The RPD structures were aligned to the average dark state geometry using the same set of rigid residues.…”
Section: Displacement Correlated Contact Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…the first, structure from the ensemble was used to initiate the method. Following [45], in the molecular alignment step only residues with a root mean square fluctuation of less than 1.3 Å were considered. The RPD structures were aligned to the average dark state geometry using the same set of rigid residues.…”
Section: Displacement Correlated Contact Networkmentioning
confidence: 99%
“…These conformational changes were found to be fully reversible under regeneration of the resting state. Based on all-atom molecular dynamics simulations, Ganguly et al [45] have suggested that the release of the CTT is correlated to a transposition of His378 in the vicinity of the flavin cofactor. The authors furthermore argue that protonation of this histidine could enhance the conformational flexibility of the CTT.…”
Section: Introductionmentioning
confidence: 99%
“…Phototropins, cryptochromes, and blue light using flavin adenine dinucleotide (BLUF) proteins each bind a flavin derivative as a chromophore that undergoes covalent bond formation with a cysteine residue, electron transfer (ET), and proton-coupled electron transfer (PCET), respectively, during the photocycle. Understanding the fundamental mechanisms of naturally occurring photoreceptor proteins is important for engineering novel systems that use light as a tool to achieve noninvasive control of biological processes with high spatiotemporal resolution (5)(6)(7).…”
mentioning
confidence: 99%
“…In the presence of light, CRY binds to TIM and both proteins are ubiquitinated for degradation by complexes involving Ramshackle (BRWD3)/JET/Cullin4 and JET/Cullin3, respectively (Ceriani et al 1999;Koh et al 2006;Peschel et al 2009;Ozturk et al 2011Ozturk et al , 2013. Several studies suggest that light triggers the reduction of the FAD coenzyme bound within CRY, inducing a conformational change that releases the CRY carboxy-terminal tail (CTT) (Dissel et al 2004;Hoang et al 2008;Ozturk et al 2011Ozturk et al , 2008Vaidya et al 2013;Ganguly et al 2016). However, other experiments indicate that light causes CTT release through a process that does not depend on flavin reduction (Ozturk et al 2014).…”
Section: Other Kinasesmentioning
confidence: 99%